Peran Media Lokal dalam Kebencanaan: Analisis Framing Pemberitaan tentang Banjir di Ponorogo - Dwi Anggoro, Ayub; Lestarini, Niken; Pinaryo (Jurnal Audiens, 2025)
This research analyzes the role of local media in a disaster context by examining the construction of reality in flood reporting in Ponorogo by the Local Media "Kanal Ponorogo". With the dominance of hydrometeorological disasters such as floods (72% of total disaster events from 2023-2024), Ponorogo Regency was selected as the case study. Methodologically, this research is a qualitative study using the framing analysis method based on Robert N. Entman's model to dissect how Kanal Ponorogo frames the flood issue through four elements: problem definition, causal diagnosis, moral judgment, and treatment recommendation. The results of the analysis of three main news stories show that Kanal Ponorogo's reporting is dominated by a reactive and episodic pattern, focusing on disaster impacts and emergency response. The frames used vary, ranging from human interest and victim frames (highlighting the suffering of residents) to action and solution frames (emphasizing the heroic performance of the military/police). However, consistently, the reporting avoids structural analysis by simplifying flood causality solely as a natural phenomenon, without delving into root causes such as environmental governance or mitigation failures. The research concludes that while serving as a channel for citizen aspirations and providing legitimacy for authorities, the framing used has the potential to obscure the root of the problem and reduce demands for accountability. Consequently, there is a gap between the strategic potential of local media as a partner in disaster resilience and its reporting practices, which are not yet proactive.